Cognitive enhancement in video game training: two separate routes of transfer? - Oei, Chie Ming (2014)
There has been considerable interest in the last decade on action video games’ effects on human perception and cognition, with many studies showing a positive effect of video game play on a variety of cognitive and perceptual measures. However, the mechanisms of transfer have not been well characterized. Here, review of existing evidence suggests that improvements shown in transfer tasks are limited to the same skills that are frequently demanded in the trained video game, namely lower level perceptual and attentional skills. Hence, frequent practice of these skills in the video game lead to improvements in these same skills that are demanded in the transfer task. In three studies, this theory is tested. In study 1, different video games with different cognitive demands were compared. Following 20 hours of training on one of several games, participants’ improvement on various cognitive tasks matched the demands of the game that they trained in respectively. Specifically, those trained in a hidden-object game and spatial working memory game improved in visual search efficiency and spatial working memory. Search efficiency was also improved in those that played a match-3 puzzle game. By comparison, those trained in an action game improved in the attentional blink, a filter task and a multiple-object tracking task. In study 2, participants trained in a variety of shooter games with different demands. Following 20 hours of training, participants that played a fast-paced first person shooter improved in the attentional blink and multiple-object tracking, while a slower paced third person shooter training also resulted in attentional blink improvements, but to a smaller extent. Again, the improvements were limited to skills common to the trained video game and transfer task. In contrast, no transfer occurred from other action video games that did not contain demands to switch attention rapidly and track multiple objects to tasks that measured these skills. Finally, in Study 3, to test the hypothesis of a general transfer to measures of executive control, participants were Video games and cognition 5 trained to play games with different executive demands for 20 hours. The games included a first-person shooter, an arcade game, a real-time strategy game and a physics puzzle game that demanded complex problem solving, planning and reframing. Only the latter game improved all executive control as measured by task switching, inhibition, and stimulus- response interference. The results of all three studies and other studies reviewed taken together suggest two possible routes of transfer in video game training. On one hand, transfer of lower-level information-processing skills such as visual perception and attention may depend on a close match in demands between the transfer task and trained game. Conversely, transfer of higher-order executive control skills and mental flexibility may depend upon the training in more general demands such as high-level planning, strategizing, complex problem solving and reframing.